One‐Pot Synthesis of Diazirines and 15N2‐Diazirines from Ketones, Aldehydes and Derivatives: Development and Mechanistic Insight. Issue 18 (29th July 2021) - Ibert, Quentin; Cauwel, Madeleine; Glachet, Thomas; Tite, Tony; Le Nahenec‐Martel, Patricia; Lohier, Jean‐François; Renard, Pierre‐Yves; Franck, Xavier; Reboul, Vincent; Sabot, Cyrille
Abstract: Broad scope one‐pot diazirine synthesis strategies have been developed using two different oxidants depending on the nature of the starting material. In all cases, an inexpensive commercial solution of ammonia (NH3 ) in methanol (MeOH) was employed, avoiding the difficult use of liquid ammonia. With aliphatic ketones, t ‐butyl hypochlorite ( t ‐BuOCl) was found to be the best oxidant whereas it is preferable to use phenyliodine diacetate (PIDA) with aromatic ketones, aldehydes and imines. The nature of the imine‐protecting group is essential and only t ‐butyl imine allowed the synthesis of 15 N2 ‐diazirine with complete 15 N incorporation, emphasizing a key trans‐imination step in the reaction mechanism. These methods are operationally simple, and tolerant to most functional groups, providing diazirines with yields ranging from 20 to 99%. Abstract :